The Relevance of Moral Emotional Appeals in Environmental Political Debates - Egres, Dorottya (Informal Logic)

(untitled) (Informal Logic, 2025)
This paper examines the relevance of moral emotional appeals in the mixed dialogue type of public debates between politicians about environmentalism, relying on the concepts of goals and emotional appeals from the informal logical tradition. This paper argues that if argumentative moves are evaluated according to the action-producing dialogue type’s collective goal which could be pressing for action on environmentalism, and politicians take on the role of emotional entrepreneurs, then moral emotional appeals by politicians could evoke moral emotions in the audience, thus encouraging them to become more environmentally friendly. The influence of moral emotions on individual sustainable choices is based on empirical research from political and environmental sciences.